A validation study of a new instrument for low cost bite force measurement. (October 2016) - Testa, Marco; Di Marco, Anna; Pertusio, Raffaele; Van Roy, Peter; Cattrysse, Erik; Roatta, Silvestro
Abstract: Quantitative assessment of force in masticatory muscles is not a routine clinical test, probably due to the lack of an "easy-to-use" device. Aim of this study is (1) to present a low cost bite force instrument located in a custom-made housing, designed to guarantee a comfortable and effective bite action, (2) to evaluate its mechanical characteristics, in order to implement it in clinical settings and in experimental setups. Linearity, repeatability and adaptation over time were assessed on a set of four different sensors in bare and housed condition. Application of the housing to the transducer may appreciably alter the transducer's response. Calibration of the housed transducer is thus necessary in order to correctly record real bite force. This solution may represent a low cost and reliable option for biting force measurement and objective assessment of individual force control in the scientific and clinical setting.